Transesophageal echocardiography during cardiopulmonary resuscitation is associated with alternate areas of compression: Analysis of healthcare provider experiences with potential implications for conventional compressions - Rory A. Marshall; Kate DeVito-Porter; Geneviève Dallaire; Tom Jelic; Amanda Smith; Frank Myslik; Rohit Mohindra; Rajiv Thavanathan; Tracy D. Wilson; Paul Olszynski (PLoS ONE, 2026)
Background Ultrasound-guided cardiopulmonary resuscitation (UG-CPR) offers healthcare providers real-time, sonographic guidance during CPR. Transesophageal echocardiography-guided CPR (TEE-CPR) is limited to institutions with the prerequisite equipment and expertise. Learnings from TEE-CPR have the potential to improve conventional CPR methods, particularly in identification of alternate areas of compression (AOC) when conventional compressions fail. It is unclear how often, and to what extent, performing TEE-CPR compressions varies from conventional compressions. This study explored and compared healthcare provider impressions of performing chest compressions during conventional and TEE-CPR. Methods An online survey was distributed to healthcare providers working at TEE-CPR sites throughout Canada. The 34-item survey explored commonalities and differences between conventional and TEE-CPR. Quantitative and qualitative analyses were used to describe changes in the AOC, compression dynamics including changes in chest wall and compression effort, and logistical differences associated with integration into broader resuscitative choreography. Results Amongst 30 respondents from 5 distinct sites, 96.7% reported instances of TEE-CPR where the AOC was moved away from the conventional site to improve chest compression quality. Further, 76.7% of respondents indicated altering the AOC during at least half of TEE-CPR events. Alternate areas of compression were more common than the conventional AOC after initiation of TEE-CPR (pre-ultrasound conventional 25: alternative 5 versus post-ultrasound conventional 13: alternative 17, X2 (1,N = 30)=10.3, p = 0.0013). The reported shift was predominantly leftward (61.0%), then caudal (26.2%). Providers reported improved chest compression quality from real-time visual feedback. Most providers reported similar exertional effort while performing chest compressions. Conclusions Use of TEE-CPR often leads to adjustments in chest compression location, predominantly in a leftward and/or caudal direction. Performing TEE-CPR compressions was reported to have minimal impact on provider exertion as compared to conventional CPR. Prospective research mapping the locations and frequencies of alternate AOCs during TEE-CPR, and associated clinical outcomes, are warranted.